Smallville - Nutter, David; Jones Eric Johnson; Allison MackSam; John Glover; Kristin Kreuk; Michael Rosenbaum; Tom Welling (USA, Canada Warner Home Video, 2001)
A meteor shower bursts from the heavens, raining destruction on the unsuspecting citizens of Smallville. Present day. Twelve years later and the healing process has left the town's inhabitants with scars and secrets. From the ashes of tragedy, a popular yet awkward teen attemptsto decipher the meaning of his life and his clouded past. As he struggleswith the transition from boyhood to adulthood, his strength and strangeabilities set him uncomfortably apart from his peers, and his name is Clark Kent.
A young Clark Kent struggles to find his place in the world as he learns to harness his alien powers for good and deals with the typical troubles of teenage life in Smallvile.
Languages : English, French Subtitles : English, Turkish, German, French, Spanish, Italian, Russian
Keywords: Adventure -- Tv Series; Drama; SciFi; Thriller; Action